The Federal Law of Education in Argentina: Its Application in the Province of Buenos Aires - Arias, María Fernanda (Education Policy Analysis Archives, 2005)
The present work seeks to analyze the results of the educational reform of the secondary school system in Argentina initiated by the Ley Federal de Educación in 1993. This article has chosen Greater Buenos Aires, the biggest conurbation in the country, as a "case study." The methodology used is based on quantitative and qualitative surveys administered to the top authorities of state and private schools in the area. We conclude that the reactions toward the reform are, in general, negative. Furthermore, there are no differences in attitudes between private and state schools. Both of them agree that the worst effect is the leveling down of the quality of education. In other words, the main cause of disagreement is mostly pedagogic.